The relationship between training, learning and career development strategies on engineers’ intention to stay - Cheong, Chew Yee (2015)
This paper investigates the relationship between Human Resource Development (HRD) strategies and Malaysian engineers’ intention to stay working with their employing organization. It focuses on three main HRD strategies, namely training, learning and career development. A total of 97 questionnaires were distributed to engineers in a multinational oil and gas company, however only 68 were returned. The findings revealed a significant positive relationship between all three main HRD strategies and engineers’ intention to stay, whereby learning had the strongest unique contribution to explaining engineers’ intention to stay than other HRD strategies. This finding implies that learning opportunities such as challenging works, study leave, and multi-tasking role have the capacity to influence employees’ intention to continue working in the company.